"Flogging a Dead Cow?": The Revival of Malawian Chingoni (Nordic Journal of African Studies, 2002)
The paper explores how Chingoni, a language of the conquering Ngoni, lost out to Chitumbuka and Chichewa, the languages of the conquered Tumbuka and Chewa respectively, as a language of everyday communication to the extent of being moribund. Since language is usually considered to be a marker of identity, the link between the Ngoni identity and Chingoni is also explored and it is concluded that language is not a sine qua non ingredient of group identity. The paper also examines efforts being made by the Abenguni Revival Association to revive Chingoni which is now considered an endangered language. It concludes that although the efforts are laudable, it is very unlikely that they will produce positive long term results.